The problem of governance of regional authorities in Тurkey and Germany: experience of comparative analysis (Journal of history, 2023)
The shaking of the dominance of increasingly centralized structures in the world, the dominance of high competition in the economic field, the huge transformation in the field of communication and information processing technologies have both revealed the importance of fundamental rights and freedoms and changed the citizens view of public authority and state method and led to an increase in the demands and expectations for the quality and transparent performance of the public service. In this process, the structure of both central and local governments and the developments they experience gain importance. In this study, local administrations of Turkey and the Federal Republic of Germany are examined. The aim of the study is to examine local governments in Turkey and Federal Germany within the framework of the legal regulations they are subject to.  The current Constitutions of both states, the laws related to local governments and the legal regulations to which public officials working in local governments are subject are examined.Key words: Local Government, Turkey, Federal Germany